Exploring the Meta-debrief: Developing a Toolbox for Debriefing the Debrief - Kumar, Prashant; Collins, Kathleen; Oliver, Nathan; Duys, Rowan; Park-Ross, Jocelyn Frances; Paton, Catherine; Laws-Chapman, Colette; Eppich, Walter; McGowan, Neil (Simulation in healthcare : journal of the Society for Medical Simulation, 2025)
Otherwise known as debriefing the debrief, meta-debriefing describes the practice of debriefing simulation facilitators after they have facilitated, or observed, a debriefing. It is a vital component of enhancing debriefing skills, irrespective of where debriefers may be in terms of their professional development journey from novice to expert. We present the following 4 fundamental pillars, which underpin the creation of an impactful meta-debriefing strategy: theoretically driven, psychologically safe, context dependent, and formative in function. Furthermore, we describe various strategies that, underpinned by these 4 key pillars, contribute to a toolbox of techniques that enable meta-debriefers to develop proficiency and flexibility in their practice. We have synthesized and critically reviewed the current evidence base, derived mostly from the debriefing literature, and highlighted gaps to address in meta-debriefing contexts. We hope this article stimulates discussion among simulation practitioners, progresses the science and art of meta-debriefing, and prompts further research so that meta-debriefing can become an integral evidence-based component of our faculty development processes.